Expression of Aurora Kinase A and B in chondrosarcoma and its relationship with the prognosis - Liang Xiaohui; Wang Danying; Wang Yan; Zhou Zhiqiang; Zhang Juan; Li Jinsong (Diagnostic Pathology, 2012)
Abstract Purpose To investigate the expression of Aurora Kinase A and B in patients with chondrosarcoma and consider it as a prognostic marker and molecular target of therapy. Methods To evaluate the relationship of the Aurora Kinase A and B and the clinical pathological parameters and prognosis of chondrosarcoma. 72 case chondrosarcoma and 42 case chondroma were performed immunohistochemistry on the tissue microarray paraffin sections. The survival time of patients was followed-up. Results The expression of Aurora Kinase A and B in chondrosarcoma was significantly higher than that in chondroma (p<0.01). There were differences about the expression of Aurora Kinase A and B in chondrosarcoma between the recurrence group and the non-recurrence group, metastatic group and non-metastatic group (p<0.05), but not age and gender (p>0.05). The expression of Aurora Kinase A and B were significantly lower in group low grade conventional chondrosarcoma than that in groups medium and high grade conventional chondrosarcoma (p<0.01). The expression of Aurora Kinase A and B in chondrosarcoma showed a positive correlation (p<0.01). According to the Kaplan Meier analysis and multivariate Cox regression analysis, the survival rate was significantly different between the patients with positive Aurora Kinase A and the patients with negative expression (p<0.05) and Aurora Kinase A expression was an independent risk marker of survival(HR=11.263, 95%CI: 2.317–54.748, P=0.003). Conclusion Both the Aurora Kinase A and B might involve in the oncogenic, invasive and metastatic process of chondrosarcoma; however, the mechanism is still unclear. The Aurora Kinase A and B could be used as a new prognostic marker and molecular therapeutic target for chondrosarcoma. Virtual Slide The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/9101494267377096.